Secure Optical Identity Tag with Quick Response Code Based on Sparse Phase Information - Emad A. Mohammed,; Haitham L. Saadon, (University of Thi-Qar Journal of Science, 2020)
We propose, an optical identity tag authentication using quick response code with the primary information based on sparse encrypted data. The optical identity tag approved with a high security verification in some purposes such as credit cards and passports. The primary information contained in the identity tag is compressed by applying sparse representation technique to the data of encrypted function. From this proposal, an optical identity tag is implemented for authentication. Only users with correct information can achieve the authentication process whereas illegal users with false information cannot, so that the security of the system is improved. Numerical simulations and results are presented to demonstrate the performance of this optical identity tag. The performance of the system was studied by subjecting the double-image encryption and verification authentication method for occlusion attack. The obtained results explain the system was able to validate the proposed optical identity tags though when it’s under the effect of occlusion.